Communication—The Impact of TaN Barrier Processes on Different Ultra Low-k Dielectrics. (20th October 2015) - Zhang, Xunyuan; Gillot, Christophe; Zhao, Larry; Ryan, E. Todd; Wu, Chen
Abstract : TaN barriers were deposited by physical vapor and atomic layer deposition on different low-k dielectrics with dielectric constant values of 2.4, 2.55 and 2.7. The low-k damage introduced by different TaN processes was studied using metal-insulator-metal capacitors, where the k value was extracted from Capacitance-Voltage measurements. A plasma enhanced atomic layer deposition TaN process caused an increase of k value from 15% to 40% compared to physical vapor deposition TaN and thermal atomic layer deposition. Current-Voltage characteristics showed the presence of moisture impacting the behavior of plasma enhanced atomic layer deposition TaN samples corresponding to a severe plasma damage.